Making space for the dead : catacombs, cemeteries, and the reimagining of Paris, 1780-1830 - Legacey, Erin-Marie, 1979- (Cornell University Press, 2019)
"This book unearths the revolutionary history of Paris's most famous spaces for the dead, including Père Lachaise Cemetery and the Paris Catacombs, and explains how they became powerful sources of collective identity for modern France"--